Methodology of Teaching Mathematics in Primary Education - Xursanova Zilola Mirzaxolmatovna; Fozilov Jakhongir Ibrokhimovich; Raimberdieva Sharifaxon Ne'matovna (Zien Journals, 2022)
The following are some suggestions and information on the organization of mathematics teaching methods.
Keywords: Mathematics teaching methods; interactive method; analysis; synthesis